Row ratio increasing improved light distribution, photosynthetic characteristics, and yield of peanut in the maize and peanut strip intercropping system - Lu, Juntian; Dong, Qiqi; Lan, Guohu; He, Zecheng; Zhou, Dongying; Zhang, He; Wang, Xiaoguang; Liu, Xibo; Jiang, Chunji; Zhang, Zheng; Wan, Shubo; Zhao, Xinhua; et al. (Frontiers in Plant Science, 2023)
The variations of canopy microenvironment, especially the light environment, have an important impact on the photosynthetic physiological characteristics and yield formation of dwarf crops in cereal and legume intercropping system. Although different row ratio settings and strip width of dwarf crops in intercropping system have important effects on microclimate of canopy, little information is available on the effects of intercropping on chlorophyll synthesis and photosynthetic physiological characteristics of dwarf crops. A two-years field experiment was conducted in 2019 and 2020, five treatments were set up: sole maize (SM), sole peanut (SP), four rows of maize alternated with 8 rows of peanut (M4P8), four rows of maize alternated with 4 rows of peanut (M4P4), four rows of maize alternated with 2 rows of peanut (M4P2). The results showed that intercropping reduced the photosynthetic capacity of peanut in different row ratio intercropping. The light transmittance (PAR), photosynthetic rate (PN), transpiration rate (TR) and stomatal conductance (GS) of peanut canopy were reduced, while the intercellular carbon dioxide concentration (CI) were increased. The decrease of photosynthetic capacity was caused by non-stomatal factors. The change of chlorophyll synthesis in peanut is an important factor affecting the change of its photosynthetic physiological characteristics. Compared with M4M4 and M4P2, M4P8 improves the content of chlorophyll synthesis precursor and conversion efficiency, which promotes the utilization efficiency of light energy. The average ALA content in each period increased by 23.17% and 26.17%, Proto IX content increased by 20.61% and 25.82%, Mg Proto IX content increased by 35.92% and 41.85%, and Pchlide content increased by 9.40% and 9.41%. However, insufficient synthesis of ALA and limited synthesis of Mg Proto IX and transformation of Pchlide are the main reasons for the reduction of chlorophyll content in M4M4 and M4P2 treatments. The dry matter accumulation and pod yield of peanut in M4P8 treatment decreased, but the proportion of dry matter distribution in late growth period was more transferred to pods. M4P8 has the highest yield and land use efficiency and can be used as a reference row ratio configuration for maize-peanut intercropping to obtain relatively high yield benefits.